“Securing One’s Base in Ngũgĩ wa Thiong’o’s Ongoing Literary Theory”: An Interview - Ndour, Moustapha (Journal of English Language and Literature (ISSN: 2368-2132), 2018)
In this interview, Ngũgĩ wa Thiong’o shares his current ongoing thoughts on the definition of African literature, issue of language and positionality, and decolonization of African resources. Ngũgĩ argues that English and European languages are stealingAfrican literary identity. His personal commitment to write in Gĩkũyũ is less motivated by a wider readership than a concern to secure “his base”. He lays the blame on Africans for lacking self-esteem or self-conception. Decolonizing African resources, including reforming language policies, stands as a mental sanity challenge in a world where African people are stereotyped and ethnicized in comparison to their Western counterparts. He concludes his thought humorously by calling for a full control of African resources and spaces.